Assessment of Hemoglobin Variants in Patients Receiving Health Care at the Ho Teaching Hospital: A Three-Year Retrospective Study. (21st March 2020) - Awaitey, Daniel Kpodji; Akorsu, Elliot Elikplim; Allotey, Emmanuel Allote; Kwasie, David Annor; Kwadzokpui, Precious Kwablah; Tawiah, Philip Apraku; Amankwah, Stephen Adomako; Abaka-Yawson, Albert
Abstract : Background . It is estimated that one out of every three Ghanaians has hemoglobin genotype mutation. This change in genetic make-up may result in genotypes such as HbAS, HbSS, and HbSC. Many children in low- and middle-income countries die even before they are diagnosed with sickle cell disease (SCD). In Africa, there are limited data on the incidence and prevalence of SCD and the Volta region of Ghana is no exception. Aim . The aim of this study was to determine the prevalence of SCD and to assess the hemoglobin variants among patients attending Ho Teaching Hospital. Methods . A retrospective study design was used to extract information from the Hospital Administration and Management Systems (HAMS) on the hemoglobin electrophoresis results and corresponding full blood count results of the SCD and sickle cell anemia (SCA) patients as well as patients who were asked to do Hb electrophoresis irrespective of their sickling status. Data were collected for the period January 2016 to December 2018. Sickle cell disease status was determined using the Hb genotypes from the Hb electrophoresis results. The full blood count was used to categorize the severity of anemia based on the hemoglobin concentration in the SCA and SCD patients. Results . A total of 1, 523 subjects were included in the study of which the prevalence for sickle cell disease was 16.7%. The SCD genotypes included HbS (6.2%), HbSC (7.9%), and HbSF (2.6%). Hemoglobin C disease (HbCC) constituted 0.3% out of the total prevalence of SCD. The prevalence of anemia was 99.2%, with the severest form in HbS. Also, majority of the SCD patients had severe anemia. Difference in the severity of anemia was found to be significant among both male (P = 0.006 ) and female (P = 0.004 ) participants with SCD. Conclusion . Patients receiving health care at the Ho Teaching Hospital had different hemoglobin variants with HbAS recording the highest prevalence. The high incidence of hemoglobin AS implies the possibility of having an increased population of individuals with sickle cell disease in future if measures are not put in place to improve screening, counseling, and education of the public about the health threat SCD poses.